POLA KERJASAMA ANTAR LEMBAGA DALAM PENGAWASAN DAN PEMBINAAN TENAGA KERJA ASING - Hakim, Lukman; Luthfie, Muhammad; Kartakusumah , Berliana (Administratie: Jurnal Administrasi Publik, 2020)
The research objective is to find out how the pattern of cooperation between institutions in the supervision and guidance of foreign workers in Cibinong sub-district, Bogor regency. This research was conducted using a descriptive qualitative approach to determine the patterns carried out by related institutions in implementing the system/laws that have been established by the Central Government which can be implemented and run well. Guidance is carried out in order to provide understanding to employers so that they are obedient to all regulations that have been issued by the government so that they run well. Supervision of foreign workers is needed due to the increasing number of foreign workers who have entered Indonesia in order to overcome the violations committed by foreign workers who enter Indonesia under legal or illegal status. The author concludes that the pattern of cooperation between institutions in the supervision and fostering of foreign workers in Cibinong District, Bogor Regency is carried out and carried out in accordance with the Implementation guidelines and technical guidelines and regulations that have been set by the Indonesian Government so as to minimize the occurrence of violations committed by labor. Keywords: Institutions, Development, Supervision, Cooperation Patterns, Foreign Workers